Risk Difference of Stroke Based on Biological Risk Factor for Working Age Group - Eka Oktaviani Rahayu (Universitas Airlangga, 2016)
Indonesia is a country with the highest mortality of stroke in Southeast Asia. In recent cases, stroke in working age group are increasing because of unhealthy life styles in Indonesia. The aim of this research was to analyze the differences of stroke's risk based on the factors of biological risk in working age group. This research used case control method with 33 persons sample of case group and 33 persons of control group in systematic sampling. The examining variable included age, hypertension, DM type 2, hypercholesterolemia, and coronary heart disease. Then, the data were showed descriptively and analyzed by using bivariate and multivariate with Odds Ratio (OR) 95%CI and Risk Difference (RD) and logistic regression. The results showed that in working age group, the risk of hypertension 45 times higher than those without hypertension (OR = 45 95% CI = 8,75 < OR < 274,4, RD = 0,73), the risk of DM type 2 has 5,71 times higher than those without DM type 2 (OR = 5,71 95% CI = 1,26 < OR < 29,39, RD = 0,39), the risk of hypercholesterolemia has 18,6 times higher than those without hypercholesterolemia (OR = 18,6 95% CI = 3,41 < OR < 133,91, RD = 0,57), the risk of coronary heart disease has 13,91 times higher than the risk without coronary heart disease (OR = 13,91 95% CI = 1,61< OR < 311,02, RD = 0,49). It concluded that in working age group, hypertension, DM type 2, hypercholesterolemia, and coronary heart disease could increase the risk of stroke. Education about stroke is needed especially about preventing hypertension, DM type 2, hypercholesterolemia, and coronary heart disease and monitoring the stroke prone person by regulary medical check up to prevent stroke for working age group. Keywords: stroke, hypertension, DM type 2, hypercholesterolemia, coronary heart disease